FEASIBILITY OF ACCESSIBILITY IN SEKAYU VILLAGE SEMARANG - Sepli Yandri; Yeptadian Sari; Dedi Hantono (Department of Architecture Universitas Muhammadiyah Jakarta, 2021)
In urban areas, accessibility is one of significant factors to increase the economic growth. Accessibility is very important in improving community welfare. Infrastructure can also cause economic growth. Therefore, proper road infrastructure is useful for good accessibility. Development of transportation and network of road are useful to facilitate the activities in the village. As one of the urban areas in Semarang city, Sekayu village needs good accessibility as well, because Sekayu is a historic village. In this village, many old buildings have the potential to invite tourists to come to the city. Therefore, this study aims to assess the suitability of accessibility in Sekayu Village.